1999
DOI: 10.1164/ajrccm.160.5.9811002
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early, Persistent, and Late-onset Wheezing in Young Children

Abstract: Wheezing in childhood is not a single disorder and different wheezing-associated respiratory illnesses have been recently described. We investigated the association between wheezing conditions and familial, pre-, peri-, and postnatal risk factors. We studied 16,333 children, 6 to 7 yr old, enrolled in a population-based study. Standardized questionnaires were filled in by parents. A total of 1,221 children had transient early wheezing, 671 had persistent wheezing, 918 had late-onset wheezing, and 13,523 never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
138
3
14

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(177 citation statements)
references
References 36 publications
22
138
3
14
Order By: Relevance
“…[7][8][9][10][11][12] We are the first to analyze data from early childhood well into middle age. Spanning this extensive period covers the current gap in understanding of the effect of breast-feeding on asthma risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8][9][10][11][12] We are the first to analyze data from early childhood well into middle age. Spanning this extensive period covers the current gap in understanding of the effect of breast-feeding on asthma risk.…”
Section: Discussionmentioning
confidence: 99%
“…Further support comes from other studies finding that risk of early transient wheeze caused by respiratory tract infections is reduced by breast-feeding. 10,11,31 In particular, an Italian study that found breast-feeding for more than 3 months was protective against the development of transient early wheezing but was a risk factor for late-onset wheeze. 11 Why does breast-feeding appear to increase the risk of asthma and allergies after the age of 7 years?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a report published in 1999 (19), we found associations between a number of pre-, peri-, and early postnatal factors and different wheezing phenotypes in a large multicenter crosssectional population-based study, the SIDRIA (Italian Studies of Respiratory Disorders in Childhood and the Environment) phase 1 study, an extension of the International Study on Asthma and Allergies in Childhood (ISAAC) phase 1 study (20). The enrolled children were categorized, on the basis of criteria derived from Martinez and coworkers (21), as transient early wheezers (children with wheezing in the first 2 yr of life but not at school age), persistent wheezers (children who continued to wheeze at school age), late-onset wheezers (children who did not wheeze in the first years of life but who wheezed when 6-7 yr old), or nonwheezers (all other children).…”
mentioning
confidence: 98%